Hot-rolled steel sheet

CN117940597BActive Publication Date: 2026-10-13NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280060328.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-11
Filing Date
2022-09-14
Publication Date
2026-10-13
Estimated Expiration
2042-09-14

AI Technical Summary

Technical Problem

[0008]然而,在专利文献1中,没有考虑热轧钢板的极限断裂板厚减少率以及剪切加工性

Benefits of technology

[0093]根据本发明所涉及的上述方式,能够得到具有高强度以及极限断裂板厚减少率、且具有优异的延展性以及剪切加工性的热轧钢板。此外,根据本发明所涉及的上述的优选方式,能够得到在具有上述诸特性的基础上,进一步抑制了弯曲内裂纹的产生的、即耐弯曲内裂纹性优异的热轧钢板。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The hot-rolled steel sheet has a specified chemical composition. The microstructure, by area percentage, contains less than 3.0% retained austenite, more than 15.0% and less than 60.0% ferrite, and less than 5.0% pearlite. Analysis of the SEM image of the microstructure using the gray-level co-occurrence matrix method yields an entropy value greater than 10.7, an inverse difference normalized value greater than 1.020, and a cluster shading value of -8.0 × 10⁻⁸. 5 ~8.0×10 5 The standard deviation of Mn concentration is below 0.60% by mass, and the tensile strength is above 980 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hot-rolled steel sheets. Specifically, it relates to hot-rolled steel sheets that can be formed into various shapes by stamping or other processes, and particularly to hot-rolled steel sheets that have high strength, a high reduction rate in sheet thickness at the ultimate fracture, and excellent ductility and shear workability.

[0002] This application claims priority based on Japanese Patent Application No. 2021-166958 filed on October 11, 2021, the contents of which are incorporated herein by reference. Background Technology

[0003] In recent years, from the perspective of environmental protection, efforts have been made in many fields to reduce carbon dioxide emissions. Automakers have also actively developed technologies for lightweight vehicle bodies aimed at reducing fuel consumption. However, because ensuring occupant safety still prioritizes improving crashworthiness, lightweighting is not an easy task.

[0004] To balance lightweight vehicle bodies and crashworthiness, research is underway to use high-strength steel sheets to reduce the wall thickness of components. Therefore, steel sheets possessing both high strength and excellent formability are highly desirable, and several technologies have been proposed to address these requirements. Since automotive parts undergo various processing methods, the required formability varies depending on the part being applied. Among these, the reduction rate of sheet thickness at the ultimate fracture and ductility are considered important indicators of formability. The reduction rate of sheet thickness at the ultimate fracture is calculated as the minimum of the sheet thickness of the tensile test specimen before fracture and the sheet thickness of the tensile test specimen after fracture. A low reduction rate of sheet thickness at the ultimate fracture is undesirable because it leads to premature fracture when subjected to tensile strain during stamping.

[0005] Automotive parts are formed by stamping, but the blanks from this stamping process are mostly manufactured through high-productivity shearing. In blanks manufactured by shearing, excellent end-face precision is required after the shearing process.

[0006] For example, if the shape of the end face after shearing (shear end face) becomes a secondary shear surface consisting of shear surface-fracture surface-shear surface, the accuracy of the shear end face will be significantly degraded.

[0007] For example, Patent Document 1 discloses a hot-rolled steel sheet that, after stamping, controls the Mn segregation and P segregation in the central part of the sheet thickness, and becomes the raw material for a cold-rolled steel sheet with excellent surface properties.

[0008] However, Patent Document 1 does not take into account the ultimate fracture thickness reduction rate and shearing processability of hot-rolled steel sheets.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: International Publication No. 2020 / 044445

[0012] Non-patent literature

[0013] Non-patent literature 1: J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144(2018)584-596

[0014] Non-Patent Literature 2: DLNaik, HUSajid, R. Kiran, Metals 2019, 9, 546

[0015] Non-patent literature 3: K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. P.S. Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485. Summary of the Invention

[0016] The problem that the invention aims to solve

[0017] The present invention was made in view of the above-mentioned actual situation, and its purpose is to provide a hot-rolled steel sheet with high strength and ultimate fracture thickness reduction rate, as well as excellent ductility and shear workability.

[0018] The main points of this invention are as follows.

[0019] (1) The chemical composition of the hot-rolled steel sheet involved in one aspect of the present invention, in mass percent, is as follows:

[0020] C: 0.050~0.250%

[0021] Si: 0.05~3.00%

[0022] Mn: 1.00~4.00%

[0023] sol.Al: 0.001~2.000%

[0024] P: below 0.100%

[0025] S: below 0.0300%

[0026] N: below 0.1000%

[0027] O: Below 0.0100%

[0028] Ti: 0~0.500%

[0029] Nb: 0~0.500%

[0030] V: 0~0.500%

[0031] Cu: 0–2.00%

[0032] Cr: 0–2.00%

[0033] Mo: 0–1.00%

[0034] Ni: 0~2.00%

[0035] B: 0~0.0100%

[0036] Ca: 0~0.0200%

[0037] Mg: 0~0.0200%

[0038] REM: 0~0.1000%

[0039] Bi: 0~0.0200%

[0040] As: 0~0.100%

[0041] Zr: 0~1.00%

[0042] Co: 0-1.00%

[0043] Zn: 0~1.00%

[0044] W: 0~1.00%

[0045] Sn: 0–0.05%, and

[0046] The remainder consists of Fe and impurities.

[0047] Satisfying the following equations (A) and (B),

[0048] Metal structure, expressed as area %

[0049] Residual austenite is less than 3.0%.

[0050] Ferrite content is 15.0% or more and less than 60.0%.

[0051] Pearlite content less than 5.0%,

[0052] The entropy value obtained by analyzing the SEM image of the metal structure using the gray-level co-occurrence matrix method, as expressed by the following equation (1), is greater than 10.7.

[0053] The inverse difference normalized value, as expressed by equation (2) below, is greater than or equal to 1.020.

[0054] The Cluster Shade value, expressed by equation (3), is -8.0 × 10⁻⁶. 5 ~8.0×10 5 ,

[0055] The standard deviation of Mn concentration is below 0.60% by mass.

[0056] The tensile strength is above 980MPa.

[0057] 0.060%≤Ti+Nb+V≤0.500%(A)

[0058] Zr + Co + Zn + W ≤ 1.00% (B)

[0059] In formulas (A) and (B), the element symbols represent the content of the element in terms of mass % and are substituted with 0% if the element is not present.

[0060] Here, P(i,j) in equations (1) to (5) is the gray-level co-occurrence matrix, L in equation (2) is the number of gray levels that the SEM image can achieve, i and j in equations (2) and (3) are natural numbers from 1 to L, and μ in equation (3) x and μ y It is represented by the following equations (4) and (5), respectively.

[0061] [Mathematical Expression 1]

[0062] Entropy=-∑ i ∑ j P(ij).log(P(i,j))…(1)

[0063] [Mathematical Expression 2]

[0064]

[0065] [Mathematical Expression 3]

[0066]

[0067] [Mathematical Expression 4]

[0068] μ x =∑i ∑ j i(P(i,j))…(4)

[0069] [Mathematical Expression 5]

[0070] μ y =∑ i ∑ j j(P(i,j))…(5)

[0071] (2) The hot-rolled steel plate described in (1) above can also have an average crystal grain size of less than 3.0 μm on the surface.

[0072] (3) The hot-rolled steel plate described in (1) or (2) above may also contain, by mass percent, the chemical composition of the steel plate, selected from the above.

[0073] Ti: 0.001~0.500%

[0074] Nb: 0.001~0.500%

[0075] V: 0.001~0.500%

[0076] Cu: 0.01–2.00%

[0077] Cr: 0.01~2.00%

[0078] Mo: 0.01~1.00%

[0079] Ni: 0.01~2.00%

[0080] B: 0.0001~0.0100%

[0081] Ca: 0.0001~0.0200%

[0082] Mg: 0.0001~0.0200%

[0083] REM: 0.0001~0.1000%

[0084] Bi: 0.0001~0.0200%

[0085] As: 0.001~0.100%

[0086] Zr: 0.01~1.00%

[0087] Co: 0.01~1.00%

[0088] Zn: 0.01~1.00%

[0089] W: 0.01–1.00%, and

[0090] Sn: 0.01–0.05%

[0091] One or more of the groups formed.

[0092] Invention Effects

[0093] According to the above-described method of the present invention, hot-rolled steel sheets with high strength and a high reduction rate in sheet thickness at ultimate fracture, as well as excellent ductility and shear workability, can be obtained. Furthermore, according to the preferred embodiment of the present invention, hot-rolled steel sheets that, in addition to possessing the aforementioned characteristics, further suppress the generation of bending internal cracks, i.e., exhibit excellent resistance to bending internal cracks, can be obtained.

[0094] The hot-rolled steel sheet described above is suitable as an industrial raw material for use in automotive parts, mechanical structural parts, and building components. Attached Figure Description

[0095] Figure 1 This is an example of the sheared end face of the hot-rolled steel plate involved in this invention.

[0096] Figure 2 This is an example of the sheared end face of the hot-rolled steel sheet involved in the comparative example. Detailed Implementation

[0097] The chemical composition and microstructure of the hot-rolled steel sheet involved in this embodiment will be described in more detail below. However, the present invention is not limited to the structure disclosed in this embodiment, and various modifications can be made without departing from the spirit of the present invention.

[0098] In the numerical ranges specified below, marked with "~", both the lower and upper limits are included. Values ​​expressed as "less than" or "more than" are not included in the range. In the following descriptions, unless otherwise specified, percentages of chemical composition refer to mass percentages.

[0099] Chemical composition

[0100] The chemical composition of the hot-rolled steel sheet involved in this embodiment will be described in detail below.

[0101] C: 0.050~0.250%

[0102] C increases the area fraction of the hard phase and, through combination with precipitation strengthening elements such as Ti, Nb, and V, increases the strength of ferrite. When the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.060% or more, more preferably 0.070% or more, and even more preferably 0.080% or more or 0.090% or more.

[0103] On the other hand, when the carbon content exceeds 0.250%, the area fraction of ferrite decreases, thereby reducing the ductility of the hot-rolled steel sheet. Therefore, the carbon content is set to 0.250% or less. The carbon content is preferably 0.200%, 0.150%, or 0.120% or less.

[0104] Si: 0.05~3.00%

[0105] Si promotes ferrite formation, thus improving the ductility of hot-rolled steel sheets, and strengthens ferrite through solid solution, thereby increasing the strength of hot-rolled steel sheets. Furthermore, Si improves the steel's structure through deoxidation (suppressing defects such as porosity). When the Si content is less than 0.05%, these effects are not achieved. Therefore, the Si content is set to 0.05% or more. Preferably, the Si content is 0.50% or more, more preferably 0.80% or more, 1.00% or more, 1.20% or more, or 1.40% or more.

[0106] However, when the Si content exceeds 3.00%, the surface properties of the steel sheet, as well as its chemical conversion treatmentability, ductility, and weldability, deteriorate significantly, and the A3 phase transformation point increases significantly. This makes stable hot rolling difficult. Furthermore, austenite tends to remain after cooling, reducing the reduction rate of plate thickness at the ultimate fracture. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.70% or less, more preferably 2.50%, 2.20%, 2.00%, or 1.80% or less.

[0107] Mn: 1.00~4.00%

[0108] Mn has the effect of inhibiting ferrite phase transformation and thus improving the strength of hot-rolled steel sheets. When the Mn content is less than 1.00%, the desired strength cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.30% or more, more preferably 1.50% or more, or 1.80% or more.

[0109] On the other hand, when the Mn content exceeds 4.00%, due to Mn segregation, the hard phase becomes periodically banded, making it difficult to obtain the desired shear processability. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.70% or less or 3.50% or less, more preferably 3.20% or less, 3.00% or less or 2.60% or less.

[0110] Ti: 0~0.500%, Nb: 0~0.500%, V: 0~0.500%

[0111] 0.060%≤Ti+Nb+V≤0.500%(A)

[0112] In formula (A), each element symbol represents the content of that element in terms of mass %; if the element is not present, 0% is used.

[0113] Ti, Nb, and V are elements that enhance the strength of steel by finely precipitating carbides and nitrides in steel and strengthening it through precipitation. These effects cannot be achieved if the total content of Ti, Nb, and V is less than 0.060%. Therefore, the total content of Ti, Nb, and V is set to 0.060% or more. That is, the value of the side in formula (A) is 0.060% or more. Furthermore, it is not necessary to contain all of Ti, Nb, and V; containing any one of them is sufficient, and their total content is 0.060% or more. Therefore, the lower limit for the content of Ti, Nb, and V is 0%. The lower limits for the content of Ti, Nb, and V can also be set to 0.001%, 0.010%, 0.030%, or 0.050%, respectively. The total content of Ti, Nb, and V is preferably 0.080% or more, and more preferably 0.100% or more.

[0114] On the other hand, if the content of any one of Ti, Nb, and V exceeds 0.500%, or if the total content of Ti, Nb, and V exceeds 0.500%, the workability of the hot-rolled steel sheet deteriorates. Therefore, the content of each of Ti, Nb, and V is set to 0.500% or less, and the total content of Ti, Nb, and V is set to 0.500% or less. That is, the value of the side in formula (A) is set to 0.500% or less. The content of each of Ti, Nb, and V is preferably 0.400% or less or 0.300% or less, more preferably 0.250% or less, and even more preferably 0.200% or less or 0.100% or less. The total content of Ti, Nb, and V is preferably 0.300% or less, more preferably 0.250% or less, and even more preferably 0.200% or less.

[0115] sol.Al: 0.001~2.000%

[0116] Like Si, Al deoxidizes and improves steel, and promotes ferrite formation, thus increasing the ductility of hot-rolled steel sheets. When the sol.Al content is less than 0.001%, these effects are not achieved. Therefore, the sol.Al content is 0.001% or more. Preferably, the sol.Al content is 0.010% or more, 0.030% or more, or 0.050% or more, more preferably 0.080% or more, 0.100% or more, or 0.150% or more.

[0117] On the other hand, when the sol.Al content exceeds 2.000%, the above-mentioned effects become saturated, and it is not economically preferable; therefore, the sol.Al content is 2.000% or less. The sol.Al content is preferably 1.700% or less or 1.500% or less, more preferably 1.300% or less, and even more preferably 1.000% or less.

[0118] In addition, sol.Al refers to acid-soluble Al, indicating solid-solution Al that exists in steel in a solid solution state.

[0119] P: below 0.100%

[0120] Phosphorus (P) is generally present as an impurity, but it also plays a role in enhancing the strength of hot-rolled steel sheets through solid solution strengthening. The lower limit for P content is 0%, but it is permissible to include P. However, P is prone to segregation; if the P content exceeds 0.100%, the reduction in ductility and ultimate fracture thickness reduction of the hot-rolled steel sheet due to grain boundary segregation becomes significant. Therefore, the P content is 0.100% or less. Preferably, the P content is 0.050%, 0.030%, 0.020%, or 0.015% or less. The lower limit for P content does not need to be specifically specified, but it is 0%. From the viewpoint of refining cost, the lower limit for P content can also be 0.001%, 0.003%, or 0.005%.

[0121] S: below 0.0300%

[0122] Sulfur (S) is an element present as an impurity, forming sulfide inclusions in steel and reducing the ductility and reduction in thickness at the ultimate fracture point of hot-rolled steel sheets. If the S content exceeds 0.0300%, the ductility and reduction in thickness at the ultimate fracture point of the hot-rolled steel sheet decrease significantly. Therefore, the S content is 0.0300% or less. The preferred S content is 0.0100%, 0.0070%, or 0.0050% or less. The lower limit for S content is 0%, but from the viewpoint of refining cost, it can also be 0.0001%, 0.0005%, 0.0010%, or 0.0020%.

[0123] N: below 0.1000%

[0124] Nitrogen (N) is an element present in steel as an impurity, which reduces the ductility and reduction in thickness at the ultimate fracture point of hot-rolled steel sheets. When the N content exceeds 0.1000%, the ductility and reduction in thickness at the ultimate fracture point of hot-rolled steel sheets decrease significantly. Therefore, the N content is 0.1000% or less. The N content is preferably 0.0800% or less, more preferably 0.0700% or less or 0.0300% or less, and even more preferably 0.0150% or less or 0.0100% or less. The lower limit of the N content is 0%, but when the presence of one or more of Ti, Nb, and V results in a finer metal microstructure, the N content is preferably 0.0010% or more, more preferably 0.0015% or more or 0.0020% or more, to promote the precipitation of carbonitrides.

[0125] O: Below 0.0100%

[0126] If oxygen (O) is present in excessive amounts in steel, it forms coarse oxides that become the starting point for fracture, leading to brittle fracture or hydrogen-induced cracking. Therefore, the O content is 0.0100% or less. The O content is preferably 0.0080% or less, more preferably 0.0050% or less, or 0.0030% or less. The lower limit for O content is 0%, but in order to ensure a large dispersion of fine oxides during deoxidation of molten steel, the O content can also be 0.0005% or more, or 0.0010% or more.

[0127] The hot-rolled steel sheet described in this embodiment may also contain the following elements as optional elements, replacing a portion of the Fe. The lower limit for the content of these optional elements is 0%. The optional elements will be described in detail below.

[0128] Cu: 0.01–2.00%

[0129] Cr: 0.01~2.00%

[0130] Mo: 0.01~1.00%

[0131] Ni: 0.01~2.00%

[0132] B: 0.0001~0.0100%

[0133] Cu, Cr, Mo, Ni, and B all improve the hardenability of hot-rolled steel sheets. Furthermore, Cu and Mo precipitate as carbides in steel, increasing the strength of the hot-rolled steel sheet. Moreover, in the presence of Cu, Ni effectively suppresses grain boundary cracks in the slab caused by Cu. Therefore, one or more of these elements may be included.

[0134] As described above, Cu improves the hardenability of hot-rolled steel sheets and enhances their strength by precipitating as carbides at low temperatures. To reliably achieve these effects, the Cu content is preferably 0.01% or more, more preferably 0.05% or more. However, when the Cu content exceeds 2.00%, grain boundary cracks in the slab may sometimes occur. Therefore, the Cu content is 2.00% or less. The Cu content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.

[0135] As described above, Cr improves the hardenability of hot-rolled steel sheets. To reliably obtain the effects described above, it is preferable that the Cr content is 0.01% or more, more preferably 0.05% or more. However, when the Cr content exceeds 2.00%, the chemical conversion treatability of the hot-rolled steel sheet decreases significantly. Therefore, the Cr content is 2.00% or less. The Cr content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.

[0136] As described above, Mo has the effect of improving the hardenability of hot-rolled steel sheets and increasing their strength by precipitating as carbides in the steel. To reliably obtain the effects of these actions, it is preferable to have a Mo content of 0.01% or more, more preferably 0.02% or more. However, even if the Mo content exceeds 1.00%, the effects of these actions become saturated, which is not economically desirable. Therefore, the Mo content is 1.00% or less. The Mo content is preferably 0.50% or less, more preferably 0.20% or less, or 0.10% or less.

[0137] As described above, Ni improves the hardenability of hot-rolled steel sheets. Furthermore, in the presence of Cu, Ni effectively suppresses grain boundary cracks in the slab caused by Cu. To reliably obtain the effects described above, the Ni content is preferably 0.01% or more. However, since Ni is a high-valence element, a high content is not economically desirable. Therefore, the Ni content is 2.00% or less. The Ni content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.

[0138] As described above, boron (B) improves the hardenability of hot-rolled steel sheets. To reliably obtain this effect, a B content of 0.0001% or more is preferred, and more preferably 0.0002% or more. However, when the B content exceeds 0.0100%, the formability of the hot-rolled steel sheet decreases significantly; therefore, a B content of 0.0100% or less is preferred. A B content of 0.0050% or less, or 0.0025% or less, is also preferred.

[0139] Ca: 0.0001~0.0200%

[0140] Mg: 0.0001~0.0200%

[0141] REM: 0.0001~0.1000%

[0142] Bi: 0.0001~0.0200%

[0143] As: 0.001~0.100%

[0144] Ca, Mg, and REM all improve the ductility of hot-rolled steel sheets by adjusting the shape of inclusions in the steel to a preferred shape. Furthermore, Bi improves the ductility of hot-rolled steel sheets by refining the solidification structure. Therefore, one or more of these elements may be included. To reliably obtain the effects described above, it is preferable that the content of any one or more of Ca, Mg, REM, and Bi is 0.0001% or more. However, if the Ca or Mg content exceeds 0.0200%, or the REM content exceeds 0.1000%, excessive inclusions are formed in the steel, which may sometimes reduce the ductility of the hot-rolled steel sheet. Furthermore, even if the Bi content exceeds 0.0200%, the effects described above become saturated, which is not economically preferable. Therefore, the Ca and Mg contents are kept below 0.0200%, the REM content is kept below 0.1000%, and the Bi content is kept below 0.0200%. The Ca, Mg, and Bi contents are preferably 0.0100% or less, more preferably 0.0070% or less or 0.0040% or less. The REM content is preferably 0.0070% or less or 0.0040% or less. As helps improve the ductility of hot-rolled steel sheets by lowering the austenite single-phase temperature and refining the original austenite grains. To reliably obtain this effect, the As content is preferably 0.001% or more. On the other hand, even if a large amount of As is present, the above-mentioned effect is saturated, so the As content is 0.100% or less.

[0145] Here, REM refers to a total of 17 elements, consisting of Sc, Y, and the lanthanides. The REM content mentioned above refers to the total content of these elements. In the case of lanthanides, they are industrially added in the form of mixed rare earth metals.

[0146] Zr: 0.01~1.00%, Co: 0.01~1.00%, Zn: 0.01~1.00%, W: 0.01~1.00%

[0147] Zr + Co + Zn + W ≤ 1.00% (B)

[0148] The element symbols in formula (B) represent the content of the element in terms of mass % and are substituted with 0% if the element is not present.

[0149] Sn: 0.01–0.05%

[0150] Regarding Zr, Co, Zn, and W, the inventors have confirmed that even if the total content of these elements is less than 1.00%, the effect of the hot-rolled steel sheet according to this embodiment will not be impaired. Therefore, it is also possible to contain one or more of Zr, Co, Zn, and W in total of less than 1.00%. That is, the value on the left side of the formula (B) can be less than 1.00%, or less than 0.50%, less than 0.10%, or less than 0.05%. The content of each of Zr, Co, Zn, W, and Sn can also be less than 0.50%, less than 0.10%, or less than 0.05%, respectively. Since Zr, Co, Zn, and W can also be absent, their respective contents can be 0%. In order to increase the strength of the steel sheet through solid solution strengthening, the content of Zr, Co, Zn, and W can also be more than 0.01%.

[0151] Furthermore, the inventors have confirmed that even a small amount of Sn does not impair the effect of the hot-rolled steel sheet according to this embodiment. However, if a large amount of Sn is present, defects may sometimes occur during hot rolling, therefore the Sn content should be 0.05% or less. Since Sn can also be absent, the Sn content can also be 0%. To improve the corrosion resistance of the hot-rolled steel sheet, the Sn content can also be 0.01% or more.

[0152] The remaining portion of the chemical composition of the hot-rolled steel sheet involved in this embodiment may also be Fe and impurities. In this embodiment, impurities refer to impurities mixed in from the ore used as raw material, waste, or the manufacturing environment, and / or impurities that are permissible to the extent that they do not adversely affect the hot-rolled steel sheet involved in this embodiment.

[0153] The chemical composition of the hot-rolled steel sheet can be determined using general analytical methods. For example, it can be determined using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Additionally, sol and Al can be determined using ICP-AES with the filtrate obtained after heating the sample with acid. C and S can be determined using combustion-infrared absorption, N using inert gas dissolution-thermal conduction, and O using inert gas dissolution-non-dispersive infrared absorption.

[0154] When hot-rolled steel sheets have a coating on their surface, the coating can be removed by mechanical grinding or other means as needed, and then the chemical composition can be analyzed.

[0155] Metallographic structure of hot-rolled steel sheet

[0156] Next, the metal structure of the hot-rolled steel sheet involved in this embodiment will be described.

[0157] The microstructure of the hot-rolled steel sheet involved in this embodiment, in terms of area %, is as follows: retained austenite less than 3.0%, ferrite more than 15.0% and less than 60.0%, and pearlite less than 5.0%. The entropy value obtained by analyzing the SEM image of the microstructure using the gray-level co-occurrence matrix method is 10.7 or higher (represented by equation (1)), the inverse difference normalized value is 1.020 or higher (represented by equation (2)), and the cluster shading value is -8.0 × 10⁻⁸ (represented by equation (3)). 5 ~8.0×10 5 The standard deviation of Mn concentration is less than 0.60% by mass.

[0158] Therefore, the hot-rolled steel sheet according to this embodiment has high strength and a high reduction rate in thickness at the ultimate fracture, and can achieve excellent ductility and shear workability. Furthermore, in this embodiment, in a section parallel to the rolling direction, the microstructure fraction, entropy value, inverse difference normalized value, cluster shading value, and standard deviation of Mn concentration are defined at a depth of 1 / 4 of the sheet thickness from the surface (a region from 1 / 8 to 3 / 8 of the sheet thickness from the surface) and at the center of the sheet width direction. This is because the microstructure at this location represents the representative microstructure of the steel sheet.

[0159] In addition, the surface mentioned here refers to the interface between the coating and the steel sheet when the hot-rolled steel sheet has a coating.

[0160] Area ratio of retained austenite: less than 3.0%

[0161] Retained austenite is a metallic microstructure that exists in a face-centered cubic lattice even at room temperature. Retained austenite improves the ductility of hot-rolled steel sheets through transformation-induced plasticity (TRIP). On the other hand, since retained austenite transforms into high-carbon martensite during shearing, it hinders the formation of stable cracks, contributing to the formation of secondary shear surfaces and a decrease in the reduction rate of sheet thickness at ultimate fracture. When the area fraction of retained austenite is 3.0% or more, the above effects become significant, and the shearing workability of hot-rolled steel sheets deteriorates. Therefore, the area fraction of retained austenite is less than 3.0%. The area fraction of retained austenite is preferably less than 1.5%, more preferably less than 1.0%. Since less retained austenite is more preferred, the area fraction of retained austenite can also be 0%.

[0162] Methods for determining the area ratio of retained austenite include those based on X-ray diffraction, EBSP (Electron Backscattering Diffraction Pattern) analysis, and magnetic measurements. In this embodiment, the method is less susceptible to the effects of grinding (if grinding occurs, the retained austenite may sometimes transform into other phases such as martensite, thus sometimes making it impossible to determine the true area ratio), and accurate measurement results can be obtained relatively easily. The area ratio of retained austenite is determined using X-ray diffraction, which is less affected by grinding.

[0163] In the determination of the retained austenite area ratio based on X-ray diffraction in this embodiment, firstly, in a section of the hot-rolled steel sheet at a depth of 1 / 4 of the sheet thickness (the region from 1 / 8 to 3 / 8 of the sheet thickness from the surface) and at the center of the sheet width direction, parallel to the rolling direction, the Co-Kα line is used to determine the integrated intensity of six peaks: α(110), α(200), α(211), γ(111), γ(200), and γ(220). The volume fraction of retained austenite is then calculated using the intensity averaging method. The obtained volume fraction of retained austenite is considered as the area fraction of retained austenite.

[0164] Ferrite area fraction: ≥15.0% and <60.0%

[0165] Ferrite is a microstructure formed during the fcc phase transformation to bcc at relatively high temperatures. Due to its high work hardening rate, ferrite improves the strength-ductility balance of hot-rolled steel sheets. To achieve this effect, the ferrite area fraction is 15.0% or more. Preferably, it is 20.0% or more, more preferably 25.0% or more, and even more preferably 30.0% or more.

[0166] On the other hand, ferrite has low strength, so if the area fraction is excessive, the desired strength cannot be obtained. Therefore, the ferrite area fraction is less than 60.0%. Preferably, it is 50.0% or less, more preferably 45.0% or less or 40.0% or less.

[0167] Pearlite area ratio: less than 5.0%

[0168] Pearlite is a lamellar metallic structure in which cementite is precipitated in layers between ferrite. Furthermore, it is a softer metallic structure compared to bainite and martensite. If the area fraction of pearlite is 5.0% or more, carbon is consumed by the cementite contained within the pearlite, and the strength of the remaining martensite and bainite decreases, failing to achieve the desired strength. Therefore, the area fraction of pearlite is less than 5.0%. Preferably, the area fraction of pearlite is 3.0% or less, 2.0% or less, or 1.0% or less.

[0169] To improve the tensile flangeability of hot-rolled steel sheets, it is preferable to minimize the area ratio of pearlite, and more preferably, the area ratio of pearlite is 0%.

[0170] Furthermore, in the hot-rolled steel sheet involved in this embodiment, the remaining microstructure, other than retained austenite, ferrite, and pearlite, contains a hard microstructure composed of one or more of bainite, martensite, and tempered martensite, with a total area ratio exceeding 32.0% and less than 85.0%. The lower limit of these remaining microstructures can be 36.0%, 40.0%, 44.0%, 48.0%, 52.0%, or 55.0%, and the upper limit can be 82.0%, 78.0%, 74.0%, 70.0%, or 66.0%. The remaining microstructure, other than retained austenite, ferrite, and pearlite, can also be one or more of bainite, martensite, and tempered martensite.

[0171] The area ratio of the metallic microstructure was determined using the following method. A section of the plate parallel to the rolling direction was machined to a mirror finish and then ground for 8 minutes at room temperature using colloidal silica without an alkaline solution to remove strain introduced into the sample surface. At arbitrary locations along the length of the sample section, electron backscatter diffraction was used to measure a region 50 μm in length, at a depth of 1 / 4 of the plate thickness from the surface (the region from 1 / 8 to 3 / 8 of the plate thickness from the surface), and at the center of the plate width, to obtain crystal orientation information. An EBSD analysis apparatus consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 detector) was used. The vacuum level within the EBSD analysis apparatus was 9.6 × 10⁻⁶. -5Below Pa, the accelerating voltage was 15 kV, the irradiation current level was 13, and the electron beam irradiation level was 62. The observation area was 40,000 μm. 2 .

[0172] Then, a reflected electron image is captured in the same field of view. First, the layered precipitates of ferrite and cementite are identified from the reflected electron image, and the area ratio of pearlite is obtained by calculating the area ratio of these grains. Next, for grains other than those identified as pearlite that are determined to have a body-centered cubic lattice structure, the "Grain Average Misorientation" function on the "OIM Analysis" software (registered trademark) included with the EBSD analysis device is used to identify regions with a Grain Average Misorientation value of 1.0° or less as ferrite. At this point, the Grain Tolerance Angle is set to 15°, and the area ratio of ferrite is obtained by calculating the area ratio of the regions identified as ferrite.

[0173] Next, the area ratio of the regions excluding those identified as pearlite or ferrite is measured as the area ratio of the remaining microstructure (i.e., bainite, martensite, and tempered martensite). Furthermore, when it is desired to measure the combined area ratio of bainite and the combined area ratio of martensite and tempered martensite, their area ratios can be determined using the following method. Specifically, relative to the remaining regions, with the maximum value of the "Grain Average IQ" of the ferrite region set as Iα, regions exceeding Iα / 2 are extracted as bainite, and regions below Iα / 2 are extracted as "martensite or tempered martensite". The area ratio of bainite is obtained by calculating the area ratio of the extracted regions identified as bainite. Furthermore, the combined area ratio of martensite and tempered martensite is obtained by calculating the area ratio of the extracted regions identified as martensite or tempered martensite.

[0174] In this embodiment, since the area fraction of each tissue is measured by X-ray diffraction and EBSD analysis, the sum of the measured area fractions of each tissue is sometimes not 100.0%. When the sum of the area fractions of each tissue obtained by the above method is not 100.0%, the area fraction of each tissue is converted to a sum of 100.0%. For example, if the sum of the area fractions of each tissue is 103.0%, the area fraction of each tissue is multiplied by "100.0 / 103.0" to obtain the area fraction of each tissue.

[0175] Entropy value: 10.7 or higher; Inverse difference normalized value: 1.020 or higher.

[0176] To suppress the formation of secondary shear surfaces, it is crucial to form a fracture surface after sufficient shear surface formation, thus preventing early cracking from the tool tip during shearing. For this purpose, low periodicity and high homogeneity of the metal microstructure are important. In this embodiment, the formation of secondary shear surfaces is suppressed by controlling the Entropy value (E value), representing the periodicity of the metal microstructure, and the Inverse difference normalized value (I value), representing the homogeneity of the metal microstructure.

[0177] The E value indicates the periodicity of the metal structure. When the brightness is periodically arranged due to factors such as the formation of banded structures, i.e., the periodicity of the metal structure is high, the E value decreases. In this embodiment, since a metal structure with low periodicity is required, the E value needs to be increased. If the E value is less than 10.7, secondary shear surfaces are easily generated. Starting from the periodically arranged structure, a fracture surface is formed from the tip of the shearing tool in the very early stage of the shearing process, and then another shear surface is formed. Therefore, it is presumed that secondary shear surfaces are easily generated. Therefore, the E value is 10.7 or higher. Preferably, it is 10.8 or higher, more preferably 11.0 or higher. A higher E value is more preferred; there is no particular upper limit, but it can also be 13.0 or lower, 12.5 or lower, or 12.0 or lower.

[0178] The I-value indicates the uniformity of the metal structure, and increases as the area of ​​the region with a certain brightness increases. A high I-value indicates high uniformity of the metal structure. In the hot-rolled steel sheet with a ferrite area ratio of 15.0% or more and less than 60.0% in this embodiment, a highly uniform metal structure is required. Therefore, in this embodiment, it is necessary to increase the I-value. If the I-value is less than 1.020, due to the influence of precipitates within the grains and the hardness distribution caused by elemental concentration differences, cracks will form at the tip of the shearing tool in the very early stage of shearing, resulting in a fracture surface, and then a shear surface will form again. Thus, it is presumed that secondary shear surfaces are easily generated. Therefore, the I-value is 1.020 or more. Preferably, it is 1.025 or more, more preferably 1.030 or more. The higher the I-value, the more preferred. There is no particular upper limit, but it can also be 1.200 or less, 1.150 or less, or 1.100 or less.

[0179] Cluster Shade value: -8.0×10 5 ~8.0×10 5

[0180] The Cluster Shade (CS) value indicates the skewness of a metallic structure. The CS value is relative to the average brightness of the image obtained from photographing the metallic structure. A positive value indicates a larger number of points with brightness exceeding the average, while a negative value indicates a larger number of points with brightness below the average.

[0181] In secondary electron images from a scanning electron microscope, the brightness increases in areas with large surface irregularities and decreases in areas with small surface irregularities. The surface irregularities of the object are greatly affected by the grain size and intensity distribution within the metal microstructure. In this embodiment, the CS value increases when the intensity deviation of the metal microstructure is large or the microstructure unit is small, and decreases when the intensity deviation is small or the microstructure unit is large.

[0182] In this implementation, it is important to keep the CS value within the desired range, close to 0. If the CS value is less than -8.0 × 10⁻⁶, 5 The reduction rate of the ultimate fracture thickness of hot-rolled steel sheet decreases. This is presumably because large grains exist in the metal microstructure, and these grains preferentially fail during ultimate deformation. Therefore, the CS value is -8.0 × 10⁻⁶. 5 The above. Preferably -7.5 × 10⁻⁶. 5 The above is further preferred to be -7.0×10 5 above.

[0183] On the other hand, if the CS value exceeds 8.0 × 10 5 The reduction rate of the ultimate fracture thickness of hot-rolled steel sheet decreases. This is presumably because the microscopic strength deviation in the metal structure is large, and the strain during ultimate deformation is concentrated locally, making it prone to fracture. Therefore, the CS value is 8.0 × 10⁻⁶. 5 The following is preferred: 7.5 × 10⁻⁶ 5 The following is a further preferred value: 7.0 × 10 5 the following.

[0184] The E value, I value, and CS value can be obtained using the following methods.

[0185] In this embodiment, the SEM image (secondary electron image from a scanning electron microscope) taken for calculating the E, I, and CS values ​​is located in a section of the plate thickness parallel to the rolling direction, at a depth of 1 / 4 of the plate thickness from the surface (a region from 1 / 8 to 3 / 8 of the plate thickness from the surface), and at the center of the plate width. During SEM image acquisition, a Hitachi High Technology SU-6600 Schottky electron gun is used, with a tungsten emitter and an accelerating voltage of 1.5 kV. Under these settings, the SEM image is output at 1000x magnification and 256 gray levels.

[0186] Next, the SEM image obtained by cropping an 880×880 pixel region (the observation area is 160μm×160μm in actual size) was subjected to smoothing processing as described in Non-Patent Document 3, with a contrast enhancement limiting factor of 2.0 and a tiling grid size of 8×8. Except for 90 degrees, the SEM image after smoothing was rotated counterclockwise in 1-degree increments from 0 degrees to 179 degrees, and images were created for each degree, resulting in a total of 179 images. Then, for each of these 179 images, the GLCM method described in Non-Patent Document 1 was used to collect the frequency values ​​of brightness between adjacent pixels in a matrix format.

[0187] Let k be the rotation angle starting from the original image, and the matrix of 179 frequency values ​​collected using the above method is represented as p. k (k = 0...89, 91...179). For each image, the generated p will be applied to all k (k = 0...89, 91...179). k After summing, a 256×256 matrix P is calculated, which is normalized so that the sum of each component is 1. Then, the E value, I value and CS value are calculated respectively using the following formulas (1) to (5) described in Non-Patent Document 2.

[0188] In equations (1) to (5) below, P(i,j) is the gray-level co-occurrence matrix, and the value of the i-th row and j-th column of matrix P is expressed as P(i,j). In addition, as mentioned above, a 256×256 matrix P is used for calculation, so if it is desired to enhance this point, equations (1) to (5) below can be modified to equations (1') to (5') below.

[0189] Here, L in equation (2) below is the number of grayscale levels that the SEM image can achieve. In this embodiment, as described above, since the SEM image is output with 256 grayscale levels, L is 256. i and j in equations (2) and (3) below are natural numbers from 1 to L, and μ in equation (3) below... x and μ y As shown in equations (4) and (5) below, respectively.

[0190] In the following equations (1') to (5'), the value of matrix P in the i-th row and j-th column is expressed as P ij .

[0191] [Mathematical Expression 6]

[0192] Entropy=-∑ i ∑ j P(i,j).log(P(i,j))…(1)

[0193] [Mathematical Expression 7]

[0194]

[0195] [Mathematical Expression 8]

[0196] Cluster Shade = ∑ i ∑ j (i+j-μ x -μ y ) 3 P(i,j)…(3)

[0197] [Mathematical Expression 9]

[0198]

[0199] [Mathematical Expression 10]

[0200] μ y =∑ i ∑ j j(P(i,j))…(5)

[0201] [Mathematical Expression 11]

[0202]

[0203] [Mathematical Expression 12]

[0204]

[0205] [Mathematical Expression 13]

[0206]

[0207] [Mathematical Expression 14]

[0208]

[0209] [Mathematical Expression 15]

[0210]

[0211] Standard deviation of Mn concentration: below 0.60% by mass

[0212] In this embodiment, the standard deviation of the Mn concentration at a depth of 1 / 4 of the plate thickness from the surface (a region from 1 / 8 to 3 / 8 of the plate thickness from the surface) and at the center of the plate width in the hot-rolled steel sheet is 0.60% by mass or less. This allows for uniform dispersion of the hard phase, preventing cracking from the tip of the shearing tool in the very early stages of shearing. As a result, the formation of secondary shear surfaces can be suppressed. The standard deviation of the Mn concentration is preferably 0.55% by mass or less, or 0.50% by mass or less, more preferably 0.47% by mass or less, or 0.45% by mass or less. From the viewpoint of suppressing excessive burrs, a smaller lower limit for the Mn concentration is preferred, but due to manufacturing process limitations, the practical lower limit is 0.10% by mass. If necessary, the lower limit can also be 0.20% by mass or 0.28% by mass.

[0213] After mirror polishing of the thickness section of a hot-rolled steel sheet parallel to the rolling direction, the standard deviation of Mn concentration was measured at a depth of 1 / 4 of the sheet thickness (ranging from 1 / 8 to 3 / 8 of the sheet thickness) along the width direction using an electron probe microanalysis (EPMA). The measurement conditions included an accelerating voltage of 15 kV and a magnification of 5000x, measuring the Mn concentration distribution within a 20 μm range along both the rolling and thickness directions. More specifically, the measurement interval was set to 0.1 μm, measuring the Mn concentration at over 40,000 locations. The standard deviation of the Mn concentration was then calculated based on the Mn concentration obtained from all measurement points.

[0214] Average crystal grain size of the surface layer: less than 3.0 μm

[0215] By refining the grain size of the surface crystals, bending internal cracks in hot-rolled steel sheets can be suppressed. The higher the strength of the hot-rolled steel sheet, the easier it is for cracks (hereinafter referred to as bending internal cracks) to form from the inside of the bend during bending processing. The mechanism of bending internal cracks is presumed as follows: During bending processing, compressive stress is generated on the inside of the bend. Initially, the inside of the bend deforms uniformly throughout the process, but if the amount of material processed increases, uniform deformation alone is insufficient to bear the deformation, and strain concentrates locally, thus deformation progresses (generating shear deformation bands). As these shear deformation bands further grow, cracks originate from the inside of the bend and grow along the shear bands. The reason why bending internal cracks are more likely to form with increasing strength is presumed to be that the decrease in work hardening energy associated with increasing strength makes uniform deformation difficult, leading to deformation deviations and thus the formation of shear deformation bands in the early stages of processing (or under slow processing conditions).

[0216] According to the research of the inventors, bending cracks become significant in steel sheets with a tensile strength of 980 MPa or higher. Furthermore, the inventors have found that the finer the grain size of the surface layer of the hot-rolled steel sheet, the more suppressed the local strain concentration, and the less likely bending cracks are to occur. To achieve the above-mentioned effect, the average grain size of the surface layer of the hot-rolled steel sheet is preferably less than 3.0 μm. Therefore, in this embodiment, the average grain size of the surface layer can also be less than 3.0 μm. The average grain size of the surface layer is more preferably 2.7 μm or less or 2.5 μm or less. The lower limit of the average grain size of the surface region is not particularly specified and can also be 0.5 μm or 1.0 μm.

[0217] In this embodiment, the surface layer refers to the area from the surface of the hot-rolled steel sheet to a depth of 50 μm. As described above, the surface referred to here is the interface between the coating and the steel sheet when the hot-rolled steel sheet has a coating.

[0218] The surface crystal grain size was determined using EBSP-OIM (Electron Backscatter Diffraction Pattern-Orientation Image Microscopy). EBSP-OIM was performed using a combination of a scanning electron microscope and an EBSP analysis device, along with OIMAnalysis (a registered trademark) from AMETEK. The analyzable area for EBSP-OIM is the area observable by SEM. While also depending on the SEM resolution, EBSP-OIM allows analysis at a minimum resolution of 20 nm.

[0219] In a section of hot-rolled steel sheet parallel to the rolling direction, at a depth of 50 μm from the surface and at the center of the sheet width, analysis was performed in at least five fields of view within a 40 μm × 30 μm region at a magnification of 1200x. Grain boundaries were defined as locations where the angular difference between adjacent measurement points was greater than 5°, and the area-averaged grain size was calculated. This area-averaged grain size was taken as the average grain size of the surface layer.

[0220] Furthermore, since retained austenite is not a structure formed under phase transformations below 600°C and does not have the effect of dislocation accumulation, it is not an analytical object in this method (method for determining the average grain size of the surface layer). In cases where the area fraction of retained austenite is 0%, it is not necessary to exclude it from the analysis. However, in cases where it might affect the determination of the average grain size of the surface layer, the EBSP-OIM method excludes retained austenite with an fcc crystal structure from the analysis.

[0221] Tensile strength properties

[0222] The tensile strength characteristics (tensile strength and total elongation) of the mechanical properties of hot-rolled steel sheets were evaluated based on JIS Z 2241:2011. The test specimen was specimen No. 5 of JIS Z 2241:2011. The tensile test specimen was collected from the end quarter of the sheet width, and the direction perpendicular to the rolling direction was taken as the length direction.

[0223] The tensile strength (TS) of the hot-rolled steel sheet involved in this embodiment is 980 MPa or higher. Preferably, it is 1000 MPa or higher. If the tensile strength is less than 980 MPa, the application components are limited, and the contribution to the lightweighting of the vehicle body is small. There is no need to specifically limit the upper limit, but from the viewpoint of suppressing die wear, it can also be 1780 MPa.

[0224] Furthermore, the total elongation of the hot-rolled steel sheet involved in this embodiment is preferably 10.0% or more, and the product of tensile strength and total elongation (TS×EI) is preferably 13000 MPa·% or more. The total elongation is more preferably 11.0% or more, and even more preferably 13.0% or more. Furthermore, the product of tensile strength and total elongation is more preferably 14000 MPa·% or more, and even more preferably 15000 MPa·%MPa or more. By ensuring that the total elongation is 10.0% or more and the product of tensile strength and total elongation is 13000 MPa·% or more, the application components are not limited, and significant contributions can be made to vehicle body weight reduction. An upper limit for the product of tensile strength and total elongation is not required, but it can also be 22000 MPa·% or 18000 MPa·%. An upper limit for the total elongation is not required, but it can also be 30.0%, 25.0%, or 22.0%.

[0225] Plate thickness

[0226] The thickness of the hot-rolled steel sheet involved in this embodiment is not particularly limited and can be 0.5 to 8.0 mm. When the thickness of the hot-rolled steel sheet is less than 0.5 mm, it is sometimes difficult to ensure the rolling completion temperature, and the rolling load becomes too large, making hot rolling difficult. Therefore, the thickness of the hot-rolled steel sheet involved in this embodiment can also be 0.5 mm or more. Preferably, it is 1.2 mm or more, 1.4 mm or more, or 1.8 mm or more. On the other hand, when the thickness exceeds 8.0 mm, it becomes difficult to refine the metal structure, and it is sometimes difficult to obtain the aforementioned metal structure. Therefore, the thickness can also be 8.0 mm or less. Preferably, it is 6.0 mm or less, 5.0 mm or less, or 4.0 mm or less.

[0227] Coating

[0228] The hot-rolled steel sheet of this embodiment, having the aforementioned chemical composition and metallic structure, can also be surface-treated with a coating to improve corrosion resistance. The coating can be an electroplated coating or a hot-dip coating. Examples of electroplated coatings include electroplated zinc and electroplated Zn-Ni alloys. Examples of hot-dip coatings include hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminizing, hot-dip Zn-Al alloying, hot-dip Zn-Al-Mg alloying, and hot-dip Zn-Al-Mg-Si alloying. The coating amount is not particularly limited and can be the same as conventional coatings. Furthermore, appropriate chemical conversion treatment (e.g., coating and drying with a silicate-based chromium-free chemical conversion solution) can be performed after plating to further improve corrosion resistance.

[0229] Manufacturing conditions

[0230] A preferred manufacturing method for the hot-rolled steel sheet having the above-described chemical composition and metallic structure according to this embodiment is as follows.

[0231] In the preferred manufacturing method of the hot-rolled steel sheet according to this embodiment, the following steps (1) to (10) are performed sequentially. Furthermore, in this embodiment, the temperature of the slab and the temperature of the steel sheet refer to the surface temperature of the slab and the surface temperature of the steel sheet, respectively. Additionally, stress refers to the tension applied in the rolling direction of the steel sheet.

[0232] (1) After holding the slab in a temperature range of 700 to 850°C for more than 900 seconds, further heat it and hold it in a temperature range of 1100°C or higher for more than 6000 seconds.

[0233] (2) Hot rolling is carried out in the temperature range of 850 to 1100℃ to reduce the total thickness of the plate by more than 90%.

[0234] (3) Apply a stress load of 170 kPa or more to the steel plate after the rolling of the previous section and before the rolling of the final section from the final section of hot rolling.

[0235] (4) Hot rolling is completed in such a way that the reduction rate of the final section of hot rolling is more than 8% and the rolling completion temperature Tf is more than 900°C and less than 1010°C.

[0236] (5) After the final stage of hot rolling and the steel plate is cooled to 800°C, the stress on the steel plate is less than 200 kPa.

[0237] (6) Within 1 second after hot rolling, the temperature is cooled to a temperature range below the hot rolling completion temperature Tf-50℃, and then accelerated to a temperature range of 600-730℃ at an average cooling rate of 50℃ / s or higher. Among these, cooling to a temperature range below the hot rolling completion temperature Tf-50℃ within 1 second after hot rolling is a more preferred cooling condition.

[0238] (7) Slow cooling with an average cooling rate of less than 5℃ / s for more than 2.0 seconds in the temperature range of 600 to 730℃.

[0239] (8) After slow cooling is completed, cooling is carried out in a manner with an average cooling rate of more than 30℃ / s and less than 50℃ / s in the temperature range of 450 to 600℃.

[0240] (9) Cooling is performed in a manner with an average cooling rate of 50°C / s or more in the temperature range of winding temperature ~450°C.

[0241] (10) Winding is performed in a temperature range below 350℃.

[0242] By employing the above manufacturing method, hot-rolled steel sheets with high strength, a high reduction rate in plate thickness at ultimate fracture, excellent ductility, and excellent shear workability can be stably manufactured. Specifically, by appropriately controlling the slab heating and hot rolling conditions to reduce Mn segregation and achieve equiaxed austenite before phase transformation, combined with the cooling conditions after hot rolling (described later), hot-rolled steel sheets with the desired microstructure can be stably manufactured.

[0243] (1) Slab, slab temperature during hot rolling and holding time

[0244] The slabs supplied for hot rolling can be slabs obtained by continuous casting or slabs obtained by casting and roughing. In addition, materials to which they have been subjected to hot or cold working can be used, as needed.

[0245] For hot-rolled slabs, it is preferable to hold them in a temperature range of 700–850°C for at least 900 seconds during heating, followed by further heating, and then holding them in a temperature range of 1100°C or higher for at least 6000 seconds. Furthermore, during the holding period in the 700–850°C temperature range, the steel plate temperature can be varied within that range or kept constant. Similarly, during the holding period in the 1100°C or higher temperature range, the steel plate temperature can be varied within that range or kept constant.

[0246] During the austenitic phase transformation in the temperature range of 700–850 °C, Mn is distributed between ferrite and austenite. By extending the transformation time, Mn can diffuse within the ferrite region. This eliminates micro-segregation of Mn in the slab and significantly reduces the standard deviation of Mn concentration. Furthermore, by maintaining a temperature range above 1100 °C for more than 6000 seconds, uniform austenite grains can be achieved during slab heating.

[0247] Hot rolling preferably uses a reversible mill or a tandem mill for multi-pass rolling. In particular, from the viewpoint of industrial productivity and stress load on the steel plate during rolling, it is more preferable that at least the last two stages are hot rolling using a tandem mill.

[0248] (2) Hot rolling reduction rate: a reduction of more than 90% in plate thickness within the temperature range of 850 to 1100℃.

[0249] By performing hot rolling at a temperature range of 850–1100°C, resulting in a total thickness reduction of over 90%, the main goal is to refine the recrystallized austenite grains and promote the accumulation of strain energy within the non-recrystallized austenite grains. Furthermore, it promotes austenite recrystallization and Mn atomic diffusion, reducing the standard deviation of Mn concentration. Therefore, hot rolling at a temperature range of 850–1100°C with a total thickness reduction of over 90% is preferable.

[0250] In addition, the reduction in plate thickness in the temperature range of 850 to 1100°C means that when the initial entry plate thickness before rolling in the rolling process of this temperature range is set as t0 and the exit plate thickness after rolling in the final stage of the rolling process of this temperature range is set as t1, it can be represented by {(t0-t1) / t0}×100(%).

[0251] (3) Stress above 170 kPa from the end of the hot rolling process to the end of the hot rolling process.

[0252] Preferably, the stress on the steel sheet after the rolling of the section preceding the final stage of hot rolling and before the final stage is 170 kPa or more. This reduces the number of grains with the {110}<001> crystal orientation in the recrystallized austenite after the rolling of the section preceding the final stage. Since {110}<001> is a difficult-to-recrystallize crystal orientation, suppressing its formation effectively promotes recrystallization based on the final stage's reduction. This results in improved banded microstructure in the hot-rolled steel sheet, reduced periodicity of the metal structure, and an increased E-value.

[0253] When the stress on the steel plate is less than 170 kPa, the desired value of E cannot always be achieved. More preferably, the stress on the steel plate is 190 kPa or higher.

[0254] The stress on the steel plate can be controlled by adjusting the rotation speed of the rolls in tandem rolling, and can be calculated by dividing the load in the rolling direction, which is measured by the rolling mill stand, by the cross-sectional area of ​​the plate passing through.

[0255] (4) The reduction rate of the final section of hot rolling: 8% or more, and the hot rolling completion temperature Tf: 900℃ or more and less than 1010℃.

[0256] The preferred hot-rolling final section has a reduction rate of 8% or more, and a hot-rolling completion temperature Tf of 900°C or more. By achieving a reduction rate of 8% or more in the final section of hot rolling, recrystallization based on the final section's reduction is promoted. This results in improved banded microstructure of the hot-rolled steel sheet, reduced periodicity of the microstructure, and an increased E value. By setting the hot-rolling completion temperature Tf to 900°C or more, excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. Consequently, ferrite formation in the final microstructure (the microstructure of the manufactured hot-rolled steel sheet) can be suppressed, resulting in a high-strength hot-rolled steel sheet. Furthermore, by setting the hot-rolling completion temperature Tf to less than 1010°C, austenite grain coarsening can be suppressed, the periodicity of the microstructure can be reduced, and the E value can be adjusted to the desired value.

[0257] (5) Stress in the final stage of hot rolling, after the steel plate has cooled to 800°C: less than 200 kPa

[0258] The stress on the steel plate after the final stage of hot rolling and before it cools to 800°C is preferably less than 200 kPa. By ensuring that the stress (tension) on the steel plate in the rolling direction is less than 200 kPa, the recrystallization of austenite preferentially occurs in the rolling direction, suppressing the periodic increase of the metal structure. As a result, the E value can be made into a desired value. The stress on the steel plate is more preferably 180 MPa or less. Furthermore, the stress on the steel plate in the rolling direction can be controlled by adjusting the rotational speed of the rolling mill and the coiling device, and can be calculated by dividing the measured load in the rolling direction by the cross-sectional area of ​​the plate through which it passes.

[0259] (6) After the hot rolling is completed, the temperature is cooled to below the hot rolling completion temperature Tf-50℃ within 1 second. Then, the temperature is accelerated to 600-730℃ at an average cooling rate of more than 50℃ / s.

[0260] To suppress the growth of austenite grains refined by hot rolling, it is preferable to cool by 50°C or more within one second after hot rolling. To cool to a temperature range below the hot rolling completion temperature Tf-50°C within one second after hot rolling, cooling with a high average cooling rate should be performed immediately after hot rolling, for example, by spraying cooling water onto the steel plate surface. By cooling to a temperature range below Tf-50°C within one second after hot rolling, the surface grain size can be refined, thereby improving the resistance of the hot-rolled steel plate to internal bending cracks.

[0261] Furthermore, after the aforementioned cooling, by accelerating cooling to a temperature range below 730°C at an average cooling rate of 50°C / s or higher, the formation of ferrite and pearlite, which have low strengthening properties, can be suppressed. This results in an increase in the strength of the hot-rolled steel sheet. The average cooling rate referred to here is the value obtained by dividing the temperature drop of the steel sheet from the start of accelerated cooling (when the steel sheet is introduced into the cooling equipment) to the completion of accelerated cooling (when the steel sheet is removed from the cooling equipment) by the time required from the start to the completion of accelerated cooling.

[0262] There is no specific upper limit to the cooling rate, but increasing the cooling rate will increase the size of the cooling equipment and raise its cost. Therefore, considering equipment cost, a rate of 300°C / s or lower is preferred. Furthermore, for the purpose of slow cooling as described later, the cooling stop temperature for accelerated cooling can be above 600°C.

[0263] (7) Slow cooling with an average cooling rate of less than 5°C / s for more than 2.0 seconds within a temperature range of 600–730°C.

[0264] By subjecting the steel sheet to slow cooling at an average rate of less than 5°C / s for more than 2.0 seconds within a temperature range of 600–730°C, the precipitated and strengthened ferrite can be fully precipitated. This allows for a balance between the strength and ductility of the hot-rolled steel sheet.

[0265] In addition, the average cooling rate mentioned here refers to the value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of accelerated cooling to the cooling stop temperature of slow cooling by the time required from the end of accelerated cooling to the end of slow cooling.

[0266] The preferred slow cooling time is 3.0 seconds or more. The upper limit of the slow cooling time is determined by the equipment layout, but it can be approximately less than 10.0 seconds. In addition, there is no specific lower limit for the average cooling rate of slow cooling, but since heating up without cooling involves a large investment in the equipment, it can also be 0°C / s or more.

[0267] (8) After slow cooling is completed, cooling shall be carried out in a manner with an average cooling rate of more than 30℃ / s and less than 50℃ / s in the temperature range of 450 to 600℃.

[0268] After the aforementioned slow cooling is completed, cooling is preferably performed at an average cooling rate of 30°C / s or more but less than 50°C / s within the temperature range of 450–600°C. By ensuring an average cooling rate of 30°C / s or more but less than 50°C / s within this temperature range, the desired CS value can be achieved. When the average cooling rate exceeds 50°C / s, a flat, strip-like structure with low brightness is easily formed, resulting in a CS value less than -8.0 × 10⁻⁶. 5When the average cooling rate is less than 30℃ / s, carbon is concentrated in the untransformed portion, increasing the strength of the hard structure and widening the strength difference with the soft structure, thus resulting in a CS value exceeding 8.0×10⁻⁶. 5 .

[0269] In addition, the average cooling rate mentioned here refers to the value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of slow cooling with an average cooling rate of less than 5℃ / s to the cooling stop temperature of cooling with an average cooling rate of more than 30℃ / s and less than 50℃ / s by the time required from the end of slow cooling with an average cooling rate of less than 5℃ / s to the end of cooling with an average cooling rate of more than 30℃ / s and less than 50℃ / s.

[0270] (9) Average cooling rate in the temperature range of winding temperature ~450℃: 50℃ / s or more

[0271] To suppress the area ratio of pearlite and retained austenite and obtain the desired strength and formability, it is preferable to have an average cooling rate of 50°C / s or more in the temperature range of the winding temperature to 450°C. This enables the parent phase structure to become hard.

[0272] In addition, the average cooling rate mentioned here refers to the temperature drop of the steel plate from the cooling stop temperature (with an average cooling rate of 30℃ / s or more but less than 50℃ / s) to the coiling temperature, divided by the time required from the end of cooling (with an average cooling rate of 30℃ / s or more but less than 50℃ / s) to the coiling.

[0273] (10) Winding temperature: below 350℃

[0274] The winding temperature is set to below 350°C. By keeping the winding temperature below 350°C, the amount of iron carbide precipitation can be reduced, and the deviation in hardness distribution within the hard phase can be decreased. As a result, the I value can be increased, and the formation of secondary shear planes can be suppressed.

[0275] Example

[0276] Next, the effects of one aspect of the present invention will be described in more detail through embodiments. However, the conditions in the embodiments are merely examples used to confirm the feasibility and effects of implementing the present invention, and the present invention is not limited to these single examples. Various conditions can be used to achieve the purpose of the present invention as long as they do not depart from the spirit of the present invention.

[0277] Steels with the chemical compositions shown in Tables 1 and 2 were smelted and continuously cast to produce slabs with a thickness of 240–300 mm. Using the obtained slabs, hot-rolled steel sheets as shown in Tables 5 and 6 were obtained under the manufacturing conditions shown in Tables 3 and 4.

[0278] In addition, the average cooling rate of slow cooling is less than 5°C / s. Furthermore, since the winding temperature recorded in Table 4 is measured with 50°C as the lower limit, the actual winding temperature of the example recorded as 50°C is below 50°C.

[0279] For the obtained hot-rolled steel sheet, the area ratio, E value, I value, CS value, standard deviation of Mn concentration, average grain size of the surface layer, tensile strength TS, and total elongation EI of the metal structure were determined using the above method. The results are shown in Tables 5 and 6.

[0280] In addition, the remaining part of the structure consists of one or more of bainite, martensite, and tempered martensite.

[0281] Evaluation methods for the properties of hot-rolled steel sheets

[0282] Tensile properties

[0283] A hot-rolled steel sheet is deemed acceptable as having both high strength and excellent ductility if it has a tensile strength (TS) of 980 MPa or higher, a total elongation (EI) of 10.0% or higher, and a tensile strength (TS) × total elongation (EI) of 13000 MPa·% or higher. If neither of these conditions is met, the sheet is deemed unacceptable as it does not possess both high strength and excellent ductility.

[0284] Limiting reduction rate of plate thickness at fracture

[0285] The reduction rate of ultimate fracture thickness of hot-rolled steel sheet is evaluated by tensile testing.

[0286] Tensile tests were conducted using the same method as when evaluating tensile properties. With the plate thickness before the tensile test set as t1 and the minimum plate thickness at the center of the width direction of the fractured tensile test specimen set as t2, the ultimate reduction rate of plate thickness at fracture was obtained by calculating (t1-t2)×100 / t1. Five tensile tests were performed, and the ultimate reduction rate of plate thickness at fracture was obtained by calculating the average of the three values ​​after removing the maximum and minimum values.

[0287] If the reduction rate of plate thickness at the ultimate fracture point is 60.0% or higher, the hot-rolled steel sheet is deemed acceptable as having a high reduction rate of plate thickness at the ultimate fracture point. On the other hand, if the reduction rate of plate thickness at the ultimate fracture point is less than 60.0%, the hot-rolled steel sheet is deemed unacceptable as not having a high reduction rate of plate thickness at the ultimate fracture point.

[0288] Shear workability (evaluation of secondary shear surface)

[0289] The shearing workability of hot-rolled steel sheets is evaluated by punching tests.

[0290] Three punched holes were fabricated for each embodiment, with a hole diameter of 10 mm, a clearance of 10%, and a punching speed of 3 m / s. Next, the cross-sections of the punched holes perpendicular to the rolling direction and parallel to the rolling direction were embedded in resin, and the cross-sectional shapes were photographed using a scanning electron microscope. The resulting images allowed observation of... Figure 1 or Figure 2 The sheared end face shown. Additionally... Figure 1 This is an example of the sheared end face of the hot-rolled steel plate involved in this invention. Figure 2 This is an example of the sheared end face of the hot-rolled steel sheet involved in the comparative example. Figure 1 In the middle, it is the shear end face of collapsed edge-shear surface-fracture surface-burr. On the other hand, in Figure 2 In the diagram, the shear end face consists of a collapsed edge, a sheared surface, a fracture surface, and a burr. Here, a collapsed edge refers to the R-shaped smooth surface area; a sheared surface refers to the area of ​​the punched end face separated by shear deformation; a fracture surface refers to the area of ​​the punched end face separated by cracks generated near the blade tip; and a burr refers to a surface with protrusions extending from the lower surface of the hot-rolled steel sheet.

[0291] In the obtained shear end face, on both sides of the surface perpendicular to the rolling direction and on both sides of the surface parallel to the rolling direction, for example, it is found that... Figure 2 In the case of the shear surface-fracture surface-shear surface shown, it is determined that a secondary shear surface has been formed. Each punched hole is observed from four sides, totaling 12 sides. If no secondary shear surface appears on any of the sides, the hot-rolled steel sheet is deemed acceptable as having excellent shear workability, and is recorded as "None" in the table. On the other hand, even if one secondary shear surface is formed, the hot-rolled steel sheet is deemed unacceptable as not having excellent shear workability, and is recorded as "Yes" in the table.

[0292] Flexural internal crack resistance

[0293] The following bending test is used to evaluate the resistance to internal bending cracks.

[0294] Bending test pieces were obtained by cutting rectangular test pieces of 100mm × 30mm from the halfway point of the width of hot-rolled steel sheet. Tests were conducted using the V-block method (bending angle θ = 90°) based on JIS Z 2248:2006 for both bending (L-axis bending) where the bending edge is parallel to the rolling direction (L-axis) and bending (C-axis bending) where the bending edge is parallel to the direction perpendicular to the rolling direction (C-axis). The minimum bending radius without cracking was determined. Resistance to internal bending cracks was investigated. The average of the minimum bending radii along the L-axis and C-axis, divided by the sheet thickness, was used as the ultimate bending radius R / t, which was considered an index value for resistance to internal bending cracks. Hot-rolled steel sheets with R / t below 2.5 were considered to have excellent resistance to internal bending cracks.

[0295] However, regarding the presence or absence of cracks, after mirror polishing the cross-section obtained by cutting the test piece with a face parallel to the bending direction and perpendicular to the plate surface, the cracks are observed with an optical microscope. If the length of the crack observed on the inner side of the bending test piece exceeds 30 μm, it is judged that cracks are present.

[0296]

[0297]

[0298] Table 3

[0299]

[0300] An underline indicates that the manufacturing conditions are not optimal.

[0301] Table 4

[0302]

[0303] An underline indicates that the manufacturing conditions are not optimal.

[0304] Table 5

[0305]

[0306] Underlined features indicate features that are outside the scope of the invention or are not preferred.

[0307] Table 6

[0308]

[0309] Underlined features indicate features that are outside the scope of the invention or are not preferred.

[0310] As can be seen from Tables 5 and 6, the hot-rolled steel sheet involved in this invention has high strength and a high reduction rate in thickness at the ultimate fracture, as well as excellent ductility and shear workability. Furthermore, it can be seen that the hot-rolled steel sheet with an average surface grain size of less than 3.0 μm in this invention, in addition to possessing the above-mentioned characteristics, also exhibits excellent resistance to internal bending cracks.

[0311] On the other hand, it can be seen that any one or more of the hot-rolled steel plates involved in the comparative examples have deteriorated in terms of strength, ductility, reduction rate of ultimate fracture thickness, and shear workability.

[0312] Industrial availability

[0313] According to the above-described method of the present invention, hot-rolled steel sheets with high strength and a high reduction rate in sheet thickness at the ultimate fracture point, as well as excellent ductility and shear workability, can be provided. Furthermore, according to the preferred embodiment of the present invention, hot-rolled steel sheets that suppress the generation of bending internal cracks while possessing the aforementioned characteristics, i.e., exhibit excellent resistance to bending internal cracks, can be obtained.

[0314] The hot-rolled steel sheet involved in this invention is suitable as an industrial raw material for use in automotive parts, mechanical structural parts, and building components.

Claims

1. A hot-rolled steel plate, characterized in that, The chemical composition, expressed as a percentage by mass, is as follows: C:0.050~0.250%、 Si: 0.05~3.00% Mn: 1.00~4.00% sol.Al: 0.001~2.000% P: Below 0.100% S: Below 0.0300% N: below 0.1000% O: Below 0.0100% Ti: 0~0.500%, Nb: 0~0.500%, V:0~0.500%、 Cu: 0~2.00%, Cr:0~2.00%、 Mo: 0~1.00%, Ni: 0~2.00%, B:0~0.0100%、 Ca: 0~0.0200%, Mg: 0~0.0200%, REM: 0~0.1000% Bi: 0~0.0200% As: 0~0.100% Zr:0~1.00%、 Co: 0~1.00%, Zn: 0~1.00%, W:0~1.00%、 Sn: 0–0.05%, and The remainder consists of Fe and impurities. Satisfy the following equations (A) and (B). Metal structure, expressed as a percentage of area, Residual austenite is less than 3.0%. Ferrite content is 15.0% or more and less than 60.0%. Pearlite content less than 5.0%, The entropy value obtained by analyzing the SEM image of the metal structure using the gray-level co-occurrence matrix method, as expressed by the following equation (1), is 10.7 or higher. The inverse difference normalized value, expressed by the following equation (2), is greater than or equal to 1.

020. The Cluster Shade value, expressed by equation (3), is -8.0 × 10⁻⁶. 5 ~8.0×10 5 , The standard deviation of the Mn concentration at a depth of 1 / 4 of the plate thickness from the surface (i.e., 1 / 8 to 3 / 8 of the plate thickness from the surface) and at the center of the plate width in the hot-rolled steel plate is less than 0.60% by mass. This standard deviation of the Mn concentration is obtained by the following method. The process involves mirror-grinding a section of hot-rolled steel sheet parallel to the rolling direction, followed by measurement using an electron probe microanalyzer (EPMA) at a depth of 1 / 4 of the sheet thickness (i.e., 1 / 8 to 3 / 8 of the sheet thickness) along the width direction, at the center of the sample. The standard deviation of the Mn concentration is then measured. The measurement conditions are set with an accelerating voltage of 15 kV and a magnification of 5000x. Distribution images are obtained within 20 μm along both the rolling and thickness directions of the sample. The measurement interval is set to 0.1 μm, and the Mn concentration is measured at over 40,000 locations. The standard deviation is then calculated based on the Mn concentration obtained from all measurement points. The hot-rolled steel plate has a tensile strength of 980 MPa or higher. 0.060%≤Ti+Nb+V≤0.500% (A) Zr+Co+Zn+W≤1.00% (B) In equations (A) and (B), the element symbols represent the content of that element in terms of mass percentage. If the element is not present, 0% is used as the input. Here, P(i,j) in equations (1) to (5) is the gray-level co-occurrence matrix, L in equation (2) is the number of gray levels that the SEM image can achieve, i and j in equations (2) and (3) are natural numbers from 1 to L, and μ in equation (3) x and μ y Represented by the following equations (4) and (5), respectively [Mathematical Expression 1] [Mathematical Expression 2] [Mathematical Expression 3] [Mathematical Expression 4] [Mathematical Expression 5] 。 2. The hot-rolled steel plate according to claim 1, characterized in that, The average crystal grain size of the surface layer is less than 3.0 μm.

3. The hot-rolled steel plate according to claim 1 or 2, characterized in that, The chemical composition, expressed as a percentage by mass, contains one or more elements selected from the group consisting of: Ti: 0.001~0.500%, Nb: 0.001~0.500%, V:0.001~0.500%、 Cu: 0.01~2.00%, Cr:0.01~2.00%、 Mo: 0.01~1.00%, Ni: 0.01~2.00% B:0.0001~0.0100%、 Ca: 0.0001~0.0200% Mg: 0.0001~0.0200%, REM: 0.0001~0.1000% Bi: 0.0001~0.0200% As: 0.001~0.100% Zr:0.01~1.00%、 Co: 0.01~1.00%, Zn: 0.01~1.00%, W: 0.01–1.00%, and Sn: 0.01~0.05%.

Citation Information

Patent Citations

  • Water addition mechanism

    JP2021166958A

  • Hot-rolled steel sheet and production method therefor, cold-rolled steel sheet and production method therefor, production method for cold-rolled annealed steel sheet, and production method for hot-dip galvanized steel sheet

    WO2020044445A1

  • Hot-rolled steel sheet, forged steel part and production methods therefor

    CN110475890A

  • Hot rolled steel sheet

    JP2016050335A